Similar Microsatellite Allelic Distribution Between Anopheles darlingi Population Collected by Human Landing Catch or Mosquito Magnet Traps in French Guiana - Laetitia Ferraro; Sébastien Briolant; Mathieu Nacher; Samuel Vezenegho; Antoine Adde; Christophe Nguyen; Pascal Gaborit; Jean Issaly; Romuald Carinci; Vincent Pommier de Santi; Romain Girod; Isabelle Dusfour; et al. (Tropical Medicine and Infectious Disease)
Anopheles darlingi is a major malaria vector in South America. Understanding its population dynamics is critical for designing effective vector control strategies. While various Anopheles collection methods exist, they may sample distinct populations. Microsatellite genotyping across nine loci was performed to characterize An. darlingi populations, which were collected in French Guiana between 6:30 p.m. and 7:00 a.m. using human landing catch (HLC) or Mosquito Magnet® (MM) traps. Traps were arranged in a 3 × 3 Latin square design to minimize possible effects of geographical position. Pairwise FST index and discriminant analyses of principal components (DAPC) were used to make comparisons. A total of 431 An. darlingi were analyzed. No significant genetic differentiation was observed between collection methods or time slots (FST values non-significant, p > 0.25), with DAPC revealing a single genetic cluster. Despite documented phenotypic variations, no significant population structure was detected among An. darlingi sampled in a rural village in French Guiana via collection methods or time slots. These findings confirm that mosquitoes collected with these various methods or time slots are suitable for the molecular studies of An. darlingi in French Guiana. In this context, Mosquito Magnet® traps could also represent an alternative to the now controversial human landing catch.